Comparative study of cluster based routing protocols in WSN - Bhatia, Varsha; Kumawat, Sunita; Jaglan, Vivek (International Journal of Engineering and Technology, 2017)
Wireless Sensors network is a type of wireless network, used in diverse applications and has its own set of challenges. Apart from organizing and managing WSN, the main challenges include limited resources, dynamic topology and low scalability. Wireless Sensor nodes are battery operated, so energy scarceness is a major concern. The energy consumption is maximal at the time of data transmission between network devices or nodes. Various energy conservation schemes are applied in WSN; Energy Efficient Routing is one of the possible solutions. Energy Efficient Routing is used to minimize the maintenance cost of the network and maximize the performance of the node. In this paper different hierarchical cluster based routing protocols are discussed.
Keywords: Wireless Sensor Network; Clustering; Routing Protocols.